Diagnostic accuracy of severity measures of ICD-11 and DSM-5 personality disorder: clarifying the clinical landscape with the most up-to-date evidence - Hualparuca-Olivera, Luis; Caycho-Rodríguez, Tomás (Frontiers in Psychiatry, 2023)
With the implementation of new dimensional models of personality disorder (PD) in the DSM-5 and ICD-11, several investigators have developed and evaluated the psychometric properties of measures of severity. The diagnostic accuracy of these measures, an important cross-cultural metric that falls between validity and clinical utility, remains unclear. This study aimed to analyze and synthesize the diagnostic performance of the measures designed for both models. For this purpose, searches were carried out using three databases: Scopus, PubMed and Web of Science. Studies that presented sensitivity and specificity parameters for cut-off points were selected. There were no restrictions on the age and gender of the participants nor on the reference standard used or the settings. Study quality and synthesis were assessed using QUADAS-2 and MetaDTA software, respectively. Twelve studies were eligible covering self-reported and clinician-rated measures based on the ICD-11 and DSM-5 PD severity models. A total of 66.7% of the studies showed a risk of bias in more than 2 domains. The 10th and 12th studies provided additional metrics, resulting in a total of 21 studies for evidence synthesis. Adequate overall sensitivity and specificity (Se = 0.84, Sp = 0.69) of these measures were obtained; however, the cross-cultural performance of specific cut-off points could not be assessed due to the paucity of studies on the same measure. Evidence suggests that patient selection processes should mainly be improved (avoid case-control design), use adequate reference standards, and avoid only reporting metrics for the optimal cut-off point.